Bilateral double free-flaps for reconstruction of extensive chest wall defect - Gazyakan, Emre; Engel, Holger (The annals of thoracic surgery, 2012)
A 44-year-old woman presented with ulcerating stage IV breast cancer involving the chest wall. En bloc resection of the second to seventh ribs on the right side, parts of the second to eighth ribs on the left side, the sternum, the chest wall muscles, and skin was completed with immediate reconstruction using bilateral double free flaps consisting of anterior lateral thigh and tensor fascia latae elevated on the lateral circumflex femoral system and creating recipient vessels with an arteriovenous loop.